TEOLOGI HINDU DALAM YOGA BHUWANA PRAWERTI TRADISI WATUKARU DI PASRAMAN SERULING DEWATA - Indriani, Ni Putu; D.E., Relin; Sena, I Gusti Made Widya (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Hinduism believes that the concept of God is a fundamental value in religious practice (Heriyanti, 2020). Hindu theology is a universal truth about the essence of God, derived from the sacred scriptures of Hinduism (Vedas), which discuss the philosophy of divinity, known as Brahma Vidya. Brahma Vidya is the knowledge that guides humans toward awareness of their spiritual purpose. The teaching of truth is considered one of the ultimate goals in religious life, achieved through self-discipline, purification of the mind, and harmony between body and soul. One way to support this teaching is through the practice of yoga. Yoga Bhuwana Prawerti is a sequence of yoga practices rooted in the Watukaru tradition. The effective transmission and explanation of Yoga Bhuwana Prawerti to the community require an appropriate method. Therefore, this research aims to provide an accurate explanation through a study of Hindu theology in Yoga Bhuwana Prawerti of the Watukaru tradition at Pasraman Seruling Dewata, Tabanan, Bali. This research explores: 1) the existence of Yoga Bhuwana Prawerti of the Watukaru tradition; 2) the religious symbols embedded in Yoga Bhuwana Prawerti; and 3) the meaning of Hindu theology in Yoga Bhuwana Prawerti. Theories applied in this study include the Theory of Existence, the Theory of Religion, and the Theory of Symbols to analyze the research problems. The method used in this research is qualitative, involving several stages: determining the research type, identifying primary and secondary data sources, selecting research instruments, collecting data through interviews, observation, and literature studies, followed by data analysis and presentation of findings. Yoga Bhuwana Prawerti, often referred to as the